A hierarchical colored Petri net–based cyberattacks response strategy making approach for critical infrastructures. (January 2020) - Zhu, Qianxiang; Qin, Yuanqing; Zhao, Yue; Chunjie, Zhou
Critical infrastructures are essential for national security, economy, and public safety. As an important part of security protection, response strategy making provides useful countermeasures to reduce the impacts of cyberattacks. However, there have been few researches in this domain that investigate the cyberattack propagation within a station and the incident spreading process in the critical infrastructure network simultaneously, let along analyzing the relationships between security strategy making for a station and scheduling strategy for the critical infrastructure network. To tackle this problem, a hierarchical colored Petri net–based cyberattacks response strategy making approach for critical infrastructures is presented. In this approach, the relationships among cyberattacks, security measures, devices, functions, and station capacity are analyzed and described in a hierarchical way, and the system loss is calculated with the input of abnormal station capacities. Then, based on the above model, the security strategy making for a station and the scheduling strategy making for the critical infrastructure network are investigated in depth. Finally, the effectiveness of the proposed approach is demonstrated on a simulated water supply system.